Evaluation of Spiritual Management Approach on Stress in Palliative Patients - Adventy Riang Bevy Gulo; Rosetty Rita Sipayung; Siska Dwi Ningsih; Yesta Ricam Fedrik Lase; Wiwik Wiwik (Poltekkes Kemenkes Surakarta, 2025)
Background: A palliative condition refers to a progressive and incurable state, where the focus of healthcare transitions from curative measures to comprehensive support addressing physical, psychological, social, and spiritual aspects, aiming to enhance the quality of life for both patients and their families. The objectives of this study were to evaluate the effect of a Groups ‘Peer Support’ (GPS)-based spiritual management approach on reducing stress among palliative patients in a hospital setting. Method: This study employed a quantitative quasi-experimental design with a pre- and post-test approach without a control group, involving 50 respondents selected through simple random sampling. The research instruments consisted of observation sheets, the Spiritual Care Competence Scale (SCCS), and the Depression Anxiety and Stress Scales (DASS). Data were analyzed using descriptive statistics to determine respondent characteristics, the Wilcoxon Signed Rank Test to assess pre and post intervention differences, and Spearman Rank and simple linear regression tests to identify influencing factors. Results: Most respondents were male (60.0%), aged 41–50 years (34.0%), with elementary education (28.0%), and commonly diagnosed with heart disease (26.0%). The mean stress score decreased from 3.06 to 2.74 after the intervention, with the Wilcoxon test confirming a significant reduction (Z = -2.889; p = 0.004). However, spiritual management (r = 0.062; p = 0.670) and nurse competence (p = 0.601) were not significantly associated with stress levels. Conclusion: The intervention effectively reduced stress in palliative patients, although spiritual management and nurse competence were not significant predictors, suggesting that other factors contributed to stress reduction.